An economic-research-based approach to calculate community health-staffing requirements in Xicheng District, Beijing. Issue 1 (December 2016) - Yin, Delu; Yin, Tao; Yang, Huiming; Xin, Qianqian; Wang, Lihong; Li, Ninyan; Ding, Xiaoyan; Chen, Bowen
Abstract Background A shortage of community health professionals has been a crucial issue hindering the development of CHS. Various methods have been established to calculate health workforce requirements. This study aimed to use an economic-research-based approach to calculate the number of community health professionals required to provide community health services in the Xicheng District of Beijing and then assess current staffing levels against this ideal. Methods Using questionnaires, we collected relevant data from 14 community health centers in the Xicheng District, including resident population, number of different health services provided, and service volumes. Through 36 interviews with family doctors, nurses, and public health workers, and six focus groups, we were able to calculate the person-time (equivalent value) required for each community health service. Field observations were conducted to verify the duration. Results In the 14 community health centers in Xicheng District, 1752 health workers were found in our four categories, serving a population of 1.278 million. Total demand for the community health service outstripped supply for doctors, nurses, and public health workers, but not other professionals. The method suggested that to properly serve the study population an additional 64 family doctors, 40 nurses, and 753 public health workers would be required. Conclusions Our calculations indicate that significant numbers of new health professionals are required to deliver community health services. We established time standards in minutes (equivalent value) for each community health service activity, which could be applied elsewhere in China by government planners and civil society advocates.